2007
DOI: 10.1139/x06-231
|View full text |Cite
|
Sign up to set email alerts
|

The distribution and incidence of white pine blister rust in central and southeastern Wyoming and northern Colorado

Abstract: A survey of limber pine (Pinus flexilis James) to determine the geographic distribution, incidence, and severity of white pine blister rust (WPBR) throughout 13 study areas in central and southeastern Wyoming and northern Colorado was conducted from 2002 to 2004. The majority (81.1%) of the 18 719 surveyed limber pines >1.37 m tall were classified as healthy, 13.5% were declining or dying from various causes, and 5.4% were dead. WPBR was present on 278 (55%) of the 504 survey plots. Incidence of the disease ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 18 publications
4
59
0
Order By: Relevance
“…We used 238 previously sampled (Kearns and Jacobi 2007) and 270 previously unsampled stands for this study. A stratified random sample of Kearns and Jacobi's (2007) plots from [2002][2003][2004] was used to ensure a relatively equal number of plots with no or low rust incidence and high rust incidence and the presence or absence of bark beetle activity.…”
Section: Study Areas and Plot Locationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used 238 previously sampled (Kearns and Jacobi 2007) and 270 previously unsampled stands for this study. A stratified random sample of Kearns and Jacobi's (2007) plots from [2002][2003][2004] was used to ensure a relatively equal number of plots with no or low rust incidence and high rust incidence and the presence or absence of bark beetle activity.…”
Section: Study Areas and Plot Locationsmentioning
confidence: 99%
“…Fisch., and, more recently, by mountain pine beetle (Dendroctonus ponderosae Hopk.) are having an impact on limber pine (Pinus flexilis James) stands in the Rocky Mountains (Kearns and Jacobi 2007, Burns et al 2011, US Department of Agriculture [USDA] Forest Service Rocky Mountain Region 2014, Cleaver et al 2015) and are consequently affecting regeneration. C. ribicola is capable of infecting five-needle white pines in the subgenus Strobus, has a complex life cycle requiring five spore stages, and uses species of Ribes, Castilleja, and Pedicularis (McDonald et al 2006, Mulvey andHansen 2011) as alternate hosts.…”
mentioning
confidence: 99%
“…Thinning may also lead to increases in Ribes, which thrives in full sunlight. Similarly, Kearns (2007) found that the incidence of blister rust was higher on open-grown limber pines than on intermediate or overtopped trees. Thinning may be an appropriate management strategy under certain circumstances, especially if combined with pruning.…”
Section: Thinningmentioning
confidence: 82%
“…Geils, personal communication). Kearns (2007) recently completed the most comprehensive survey of central and south-central Wyoming and for the first time, reported the disease in the Medicine Bow and Sierra Madre Mountains (Kearns and Burns 2005). Incidence of WPBR was greatest in northern Wyoming Table 1-Ribes species that grow in association with white pine populations in the Rocky Mountain Region and their potential for contributing to the spread of white pine blister rust (Kearns 2005;Van Arsdel and Geils 2004 and in areas where the disease has been present for decades.…”
Section: Current Distribution Of White Pine Blister Rust In the Rockymentioning
confidence: 99%
See 1 more Smart Citation